1979
DOI: 10.1073/pnas.76.10.5124
|View full text |Cite|
|
Sign up to set email alerts
|

Triplet states in photosystem I of spinach chloroplasts and subchloroplast particles.

Abstract: We report light-induced electron paramagnetic resonance triplet spectra from samples of chloroplasts or digitonin photosystem I particles that depend upon the dark redox state of the bound acceptors of photosystem I. If the reaction centers are prepared in the redox state P-700 A X- FdB-FdA-, then upon illumination at 11K we observe a polarized chlorophyll triplet species which we interpret as arising from radical pair recombination between P-700+ and A-. This chlorophyll triplet is apparently the analog of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 33 publications
5
24
0
Order By: Relevance
“…This demonstrates the primary photochemical activity of the preparation. The ZFS parameters calculated from this EPR spectrum agree, within experimental error, with those first reported by Frank et al (1979), and also with those found in this work using FDMR detected at Af > 700 nm (see below and Table 1). This is good evidence for the identity of the triplet state measured by FDMR at A e > 700 nm with 3p700, however, it cannot be regarded as conclusive as it is well established that there is relatively little variation in ZFS parameters between different forms of Chl a (Schaafsma 1982).…”
Section: Spectral Characterisation Of Cp1supporting
confidence: 79%
See 1 more Smart Citation
“…This demonstrates the primary photochemical activity of the preparation. The ZFS parameters calculated from this EPR spectrum agree, within experimental error, with those first reported by Frank et al (1979), and also with those found in this work using FDMR detected at Af > 700 nm (see below and Table 1). This is good evidence for the identity of the triplet state measured by FDMR at A e > 700 nm with 3p700, however, it cannot be regarded as conclusive as it is well established that there is relatively little variation in ZFS parameters between different forms of Chl a (Schaafsma 1982).…”
Section: Spectral Characterisation Of Cp1supporting
confidence: 79%
“…The 3p700 is generated by the radical pair (RP) mechanism, first observed in PSI by Frank et al (1979). It contains only the 82kD/83 kD heterodimer, which binds the heterogenous population of antenna Chl a and the primary electron donor P700 and electron acceptor A0, and has lost LHCI, the 730-735nm emitting light harvesting Chl a/bprotein (Kuang et al 1984), together with the smaller polypeptides present in larger PSI particles (Scheller et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…These particles were prepared as previously described [19]. In each case, the treated suspensions were combined with an equal amount of ethylene glycol, sealed in EPR tubes, and stored at 77°K.…”
Section: Methodsmentioning
confidence: 99%
“…This represents ϳ0. 33 3 Car/P700. Wild-type PS I complexes show a flash-induced absorbance change that represents less than 0.08 3 Car/P700 ϩ (data not shown), which would suggest an increased generation of 3 Car in PS I complexes from the menB rubA mutant.…”
Section: Flash-induced Absorbance Changes In the Near-ir And Uvmentioning
confidence: 99%
“…Bottom, at later times, the polarization pattern changes into a "late" triplet signal with a (E)/A/E/A/E/(A) pattern; the sample is PS I complexes from the menB rubA mutant with Q ϭ PQ-9. The experimental conditions are as above except for a different time integration window of 7-10 s. The signal is assigned to 3 Car populated via intersystem crossing-populated 3 Chl and represents an independent photocycle in the antenna system of PS I. by 3 Car as observed optically (27) or by EPR (32)(33)(34). The same kind of triplet polarization patterns and competing excitation trapping processes were also observed in a recent study of PS I with a Met to Leu mutation of the axial ligand to the Mg 2ϩ of the primary electron acceptor A 0 (21).…”
Section: Flash-induced Absorbance Changes In the Near-ir And Uvmentioning
confidence: 99%